2020
DOI: 10.34739/zn.2019.50.01
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Metallised Textiles. The Case Study of Maturolife Project

Abstract: This article provides an overview of the Life Cycle Assessment (LCA) method which supports manufacturers’ environmental information needs by evaluation of the environmental aspects and potential influences throughout the lifetime of the product. In the article results are presented of the first phase of the life cycle assessment of metallised textiles and the context for the analysis is a new project: „Metallisation of Textiles to make Urban living for Older people more Independent & Fashionable – MATUROLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Schischke et al [ 134 ] provided guidance on how to minimize the environmental footprint of flexible and stretchable smart textiles by analyzing numerous emerging and converging technologies in terms of sustainability implications, depending on material choices and design decisions, although they concluded that more sustainable possibilities are still greatly required, e.g., recycled resources, low-impact processes, and extended products’ lifetimes. Some other studies have focused on Life Cycle Assessment (LCA) of conductive textiles: Radulescu et al [ 137 ] reviewed an LCA analysis of conductive fiber-based flexible electromagnetic shields, and Wójcik-Augustyniak et al [ 138 ] focused on an LCA case study of metallized textiles in the frame of the Maturolife project. Saleem and Zaidi [ 139 ] discussed environmental, health, and safety aspects (toxicity) of nano-sized compounds and their sustainable use in different textile applications, due to the wide range of nanomaterials and their properties (shape, size, crystallinity, porosity, agglomeration, and aggregation).…”
Section: Sustainability and End-of-life Of Conductive Textilesmentioning
confidence: 99%
“…Similarly, Schischke et al [ 134 ] provided guidance on how to minimize the environmental footprint of flexible and stretchable smart textiles by analyzing numerous emerging and converging technologies in terms of sustainability implications, depending on material choices and design decisions, although they concluded that more sustainable possibilities are still greatly required, e.g., recycled resources, low-impact processes, and extended products’ lifetimes. Some other studies have focused on Life Cycle Assessment (LCA) of conductive textiles: Radulescu et al [ 137 ] reviewed an LCA analysis of conductive fiber-based flexible electromagnetic shields, and Wójcik-Augustyniak et al [ 138 ] focused on an LCA case study of metallized textiles in the frame of the Maturolife project. Saleem and Zaidi [ 139 ] discussed environmental, health, and safety aspects (toxicity) of nano-sized compounds and their sustainable use in different textile applications, due to the wide range of nanomaterials and their properties (shape, size, crystallinity, porosity, agglomeration, and aggregation).…”
Section: Sustainability and End-of-life Of Conductive Textilesmentioning
confidence: 99%
“…Wójcik-Augustyniak, Szajczyk, Ojstršek, and Leber [36] (pp. 5-6) claim that in the era of the circular economy, the new version of the LCA motto should be "from cradle to cradle" instead of "from cradle to grave".…”
Section: Eco-efficiency In a Sustainable Development Paradigm: Concepmentioning
confidence: 99%